BALL SCREW LINEAR ACTUATOR CONTROL AND IMPLEMENTATION BY APPLYING LUGRE FRICTION MODEL - Jia, Mingpo (My University, 2018)
The linear actuator is widely used in the industrial and aerospace arenas. The application of the linear actuator varies. The ball screw type linear actuator or ball screw system is one design. The ball screw is a mechanical system that converts rotation motion into a linear motion. The ball screw linear actuator, compared with other linear actuators, has better efficiency, higher speed, less noise, and higher load capacity. Ball screw linear actuators are used in a number of areas, such as coordinated measuring machines, 3D printers, and aerospace actuators. In this research, the industrial sponsor provided a ball screw linear actuator, and they required its accuracy to be improved. The linear actuator suffers from an accuracy problem due to various reasons. One of the major problems is nonlinear friction, which makes it difficult to estimate using the simple friction model. In this thesis, a LuGre friction model is introduced and applied to the ball screw system. The sponsor’s ball screw system includes the ball screw sliding table, AC servo drive, AC servo motor, and a linear encoder sensor. The hardware control system for the ball screw system needs to be built. Therefore, this thesis describes how a custom ball screw control system was built. The control hardware ball screw system includes a microcontroller and a custom-made digital-to-analog converter. The linear encoder position sensor’s reading methods were tested and implemented in the microcontroller. A custom digital-to-analog converter was made and tested. The control algorithms based on the LuGre friction compensator are discussed and were simulated in the Matlab Simulink environment. Then, the physical implementation of the control algorithms on ball screw system hardware were made. Finally, a new proposed control method based on the LuGre friction model performed best in terms of accuracy consistence and tracking compare to the other mentioned controllers.
Keywords: BALL SCREW; LUGRE FRICTION MODEL; CONTROL